Problem Solving Ability Viewed by Learning Style on Whole Brain Teaching’s Learning Assisted Geogebra of 8th Grade Students - Astutik, Desi Hijri; Junaedi, Iwan; Waluya, St Budi (Unnes Journal of Mathematics Education Research, 2018)
Problem solving ability is one of the goals in learning mathematics and it can be developed by paying attention to student’s learning style. The aim of this study are to determine the quality of the Whole Brain Teaching learning assisted geogebra and found a pattern of problem solving ability of 8th grade students in problem solving viewed by learning style. The research uses mixed methods study with concurrent embeded design. The type of quantitative research is experimental research with nonrandomized control group. The subject of the research were 2 students of VIII-F, who chosen from each learning style. Quantitative data were tested by z-test and t-test, while the qualitative data were analyzed descriptively. Learning by Whole Brain Teaching assisted geogebra is qualified. Students of visual type can solve the problem well until the looking back stage. Students of auditorial type can solve the problem but have difficulty to looking back. Students of kinesthetic type can solve the problem but have difficulty in planning stage.